2003
DOI: 10.1074/jbc.m300212200
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylceramide and Glucosylsphingosine Modulate Calcium Mobilization from Brain Microsomes via Different Mechanisms

Abstract: We recently demonstrated that elevation of intracellular glucosylceramide (GlcCer) levels results in increased functional Ca 2؉ stores in cultured neurons, and suggested that this may be due to modulation of ryanodine receptors (RyaRs) by GlcCer (Korkotian, E., Schwarz, A., Pelled, D., Schwarzmann, G., Segal, M. and Futerman, A. H. (1999) J. Biol. Chem. 274, 21673-21678). We now systematically examine the effects of exogenously added GlcCer, other glycosphingolipids (GSLs) and their lyso-derivatives on Ca 2؉ r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
119
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(123 citation statements)
references
References 63 publications
1
119
0
3
Order By: Relevance
“…The divergent genotype-phenotype correlation between human Gaucher and mouse models has been previously documented (28). GlcSph is a putative neurotoxin that can affect neuronal calcium mobilization (2,37) and might contribute to the development of cognitive deficits in Gba1 D409V/D409V mice. The Gaucher Gba1 D409V/D409V mouse model, recapitulating some of the cardinal features of synucleinopathies, is a valuable tool to address questions of disease mechanism and potential therapy.…”
Section: Discussionmentioning
confidence: 96%
“…The divergent genotype-phenotype correlation between human Gaucher and mouse models has been previously documented (28). GlcSph is a putative neurotoxin that can affect neuronal calcium mobilization (2,37) and might contribute to the development of cognitive deficits in Gba1 D409V/D409V mice. The Gaucher Gba1 D409V/D409V mouse model, recapitulating some of the cardinal features of synucleinopathies, is a valuable tool to address questions of disease mechanism and potential therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, we did not observe a significantly altered sensitivity to cell death of the CbCln3 ⌬ex7/8/⌬ex7/8 cells to low dose thapsigargin treatment compared with wild type cells, perhaps due to the changes we observed in the other intracellular Ca 2ϩ stores, which may serve to protect the cells from Ca 2ϩ -mediated excitotoxicity. Chronic CLN3 loss-of-function has also been reported to alter lipid microdomain architecture, which may influence Ca 2ϩ channel complex formation and activity, and it has been demonstrated that glycolipids, such as the gangliosides, can alter SERCA activity (9,24,44,60,61). Hence, future work delineating the role of CLN3 in regulating lipids may shed further light on the altered Ca 2ϩ handling observed in CLN3-deficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear what mechanism is involved in the Gsp-induced ISRs. One possibility is from that Gsp mobilized the calcium via a mechanism independent of ryanodine receptor (Lloyd-Evans et al, 2003). Therefore calcium mobilization by Gsp might induce the scratch response.…”
Section: Discussionmentioning
confidence: 99%